2023
DOI: 10.1101/2023.06.23.546270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Novel mouse model of Weaver syndrome displays overgrowth and excess osteogenesis reversible with KDM6A/6B inhibition

Abstract: Weaver syndrome is a Mendelian disorder of the epigenetic machinery (MDEM) caused by germline pathogenic variants in EZH2, which encodes the predominant H3K27 methyltransferase and key enzymatic component of Polycomb repressive complex 2 (PRC2). Weaver syndrome is characterized by striking overgrowth and advanced bone age, intellectual disability, and distinctive facies. We generated a mouse model for the most common Weaver syndrome missense variant, EZH2 p.R684C. Ezh2 R684C/R684C mouse embryonic fibroblasts (… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 91 publications
0
0
0
Order By: Relevance
“…In support of these hypotheses, functional investigations have shown that single nucleotide variants in the WD40 domain of EED abolish binding to EZH2 in vitro (Denisenko et al, 1998). Mouse models encoding pathogenic EZH2 missense variants, which are predicted to result in loss of function of the PRC2 complex, phenocopy Weaver syndrome and cause excess osteogenesis and skeletal overgrowth (Gao et al, 2023). In this study, we show that loss of Eed after neural crest induction causes the opposite phenotype, resulting in craniofacial hypoplasia due to impairments in osteogenesis, mesenchymal cell proliferation, and mesenchymal stem cell differentiation.…”
Section: Discussionmentioning
confidence: 97%
“…In support of these hypotheses, functional investigations have shown that single nucleotide variants in the WD40 domain of EED abolish binding to EZH2 in vitro (Denisenko et al, 1998). Mouse models encoding pathogenic EZH2 missense variants, which are predicted to result in loss of function of the PRC2 complex, phenocopy Weaver syndrome and cause excess osteogenesis and skeletal overgrowth (Gao et al, 2023). In this study, we show that loss of Eed after neural crest induction causes the opposite phenotype, resulting in craniofacial hypoplasia due to impairments in osteogenesis, mesenchymal cell proliferation, and mesenchymal stem cell differentiation.…”
Section: Discussionmentioning
confidence: 97%